Risk of bilateral visual impairment in individuals with amblyopia: the Rotterdam study. Issue 11 (23rd May 2007) - van Leeuwen, Redmer; Eijkemans, Marinus J C; Vingerling, Johannes R; Hofman, Albert; de Jong, Paulus T V M; Simonsz, Huib J
Abstract : Background: The excess risk of bilateral visual impairment (BVI; bilateral visual acuity <0.5) among individuals with amblyopia is an argument for screening for amblyopia, but data are scarce. Methods: The risk was estimated by determining the incidence of BVI in the Rotterdam Study, a population-based cohort of subjects aged 55 years or over (n = 5220), including 192 individuals with amblyopia (3.7%). Using a multistate lifetable, the lifetime risk and excess period spent with BVI were determined. Results: The relative risk of BVI for amblyopes was 2.6 (95% confidence interval 1.4–4.5). For individuals with amblyopia, the lifetime risk of BVI was 18%, whereas they lived on average 7.2 years with BVI. For non-amblyopic individuals, these figures were 10% and 6.7 years, respectively. Conclusion: Amblyopia nearly doubles the lifetime risk of BVI and affected individuals spent an extra six months with BVI. This study provides data for future cost-effectiveness analyses.